Detection and assessment of Parkinson's disease based on gait analysis: A survey - Guo, Yao; Yang, Jianxin; Liu, Yuxuan; Chen, Xun; Yang, Guang-Zhong (Frontiers in Aging Neuroscience, 2022)
Neurological disorders represent one of the leading causes of disability and mortality in the world. Parkinson's disease (PD), for example, affecting millions of people worldwide is often manifested as impaired posture and gait. They have been used as a clinical sign for the early detection of PD, as well as an objective index for pervasive monitoring of the PD patients in daily life. This review presents the evidence that demonstrates the relationship between human gait and PD, and illustrates the role of different gait analysis systems based on vision or wearable sensors. It also provides an overview of the available automatic recognition systems for the detection and management of PD. The intervening measures for improving gait patterns are summarized, in which the smart devices for gait intervention are emphasized. This review also highlights some of the new opportunities in detecting, monitoring, and treatment of PD based on gait, enabling the development of objective biomarkers for personalized support and treatment of PD.